EDUKASI KESELAMATAN DAN KESEHATAN KERJA (K3) DI SEKOLAH MENENGAH KEJURUAN DI TANJUNG MORAWA - Kisno Kisno; Victor Mulia Marudut Siregar; Heru Sugara; Arifin Tua Purba; Saut Purba (Jurnal Abdi Insani, 2022)
Occupational Safety and Health (K3) topic is discussed in a subject in Vocational High Schools. This is certainly useful for prospective SMK graduates to reduce the risk of accidents or health problems during learning activities at school. This activity aims to educate school residents about the risk factors and dangers that can arise as a result of activities at school. This community service was carried out at the SMK Swasta Methodist Tanjung Morawa, Deli Serdang Regency, North Sumatra. This activity was carried out with PT. Emcotama as a partner from business/industrial sector. 30 students from SMK Swasta Methodist Tanjung Morawa were involved in this activity. The results showed that 94% -95% of activity participants agreed that the venue and facilities were pursuant to K3 standards. In addition, all participants stated that the instructor were eligible. In theory/practice session, 90.5% of participants agreed this activity met the K3 standards. 95% of the participants declared that the activity had benefits and added value for them. This activity was successful with the result that more than 89% of participants were satisfied with the criteria for materials, instructors, meals, and facilities during the activity. PKM activities is concluded to be run smoothly. This is shown from more than 90% of participants who understand the basics of K3 and its implementation practices that already meet K3 standards. The aspect that needs attention is the duration of the practicum which needs to be extended to get more optimal results.